Gelsemiaceae (Gentianales) expanded to include the enigmatic Asian genus Pteleocarpa. (15th July 2014) - Struwe, Lena; Soza, Valerie L.; Manickam, Sugumaran; Olmstead, Richard G.
<x xml:space="preserve">Abstract</x> The enigmatic South‐East Asian monotypic genus Pteleocarpa has been considered as a genus incertae sedis among the eudicots for a long time. Molecular data (plastid and nuclear ribosomal regions) from 44 widely sampled species across Lamiidae and phylogenetic analyses have finally clarified its familial relationships, and it is here included in Gelsemiaceae (order Gentianales). Its morphological characteristics support a placement in this family and order as a result of the presence of potential synapomorphies, such as imbricate and commonly yellow corollas, latrorse anther dehiscence, divided styles and compressed seeds. Unique characters for Pteleocarpa in Gelsemiaceae are alternate leaves and indehiscent samaras. © 2014 The Linnean Society of London, Botanical Journal of the Linnean Society, 2014, 175, 482–496.